Endurance in speed skating - Kuper, G. H.; Sterken, E. (European Journal of Training and Development, 2003)
We analyse the development of world records speed skating from 1893 to 2000 for both men and women. The historical data show that it is likely that the relation between skating speed and distance of the various events is non-linear and converges to a limit value. We pay special attention to technical innovations in speed skating, especially, the introduction of the klapskate in the 1996/1997 season, and its impact on the long-run limit value. We focus on endurance and we estimate lower bounds for world records given the current technological state of the art. We illustrate the forecasting properties of our model using the Salt Lake City 2002 Winter Games results.